2017
DOI: 10.18632/oncotarget.18311
|View full text |Cite
|
Sign up to set email alerts
|

Soluble PD-1 and PD-L1: predictive and prognostic significance in cancer

Abstract: The membrane-bound molecules programmed death 1 (PD-1) and its ligand PD-L1 (PD-1/PD-L1) belong to the immune checkpoint pathway. PD-1 pathway downregulates effector T cells in immune response, thereby causing immune suppression. Recent studies have revealed that membrane-bound PD-1 and PD-L1 also have soluble forms. These soluble forms increase the complexity and diversity of the composition and function of the PD-1/PD-L1 signaling pathway. However, the exact roles of these molecules remain unknown. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
250
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(264 citation statements)
references
References 92 publications
3
250
2
9
Order By: Relevance
“…Previous data indicated that higher levels of PD‐L1 increase the amount of ineffective T cells impairing antitumor immune response . Recently, it was shown that high sPD‐1 levels play an adjuvant role in enhancing antigen‐specific T‐cell immunity responses . Moreover, sPD‐1 and sPD‐L1 serum levels greatly contribute to tumor pathogenesis, prognosis, and treatment response .…”
Section: Clinical Parameters and Distribution Of Chl Patients At Diagmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data indicated that higher levels of PD‐L1 increase the amount of ineffective T cells impairing antitumor immune response . Recently, it was shown that high sPD‐1 levels play an adjuvant role in enhancing antigen‐specific T‐cell immunity responses . Moreover, sPD‐1 and sPD‐L1 serum levels greatly contribute to tumor pathogenesis, prognosis, and treatment response .…”
Section: Clinical Parameters and Distribution Of Chl Patients At Diagmentioning
confidence: 99%
“…10,11 Moreover, sPD-1 and sPD-L1 serum levels greatly contribute to tumor pathogenesis, prognosis, and treatment response. 11 In cHL, overexpression of PD-1 and PD-L1 in tumor tissue promotes immune escape and blockade of apoptosis of RS cells. Furthermore, this higher expression found in tumor tissue was associated with poor survival and a negative prognostic factor.…”
mentioning
confidence: 99%
“…Повышение сывороточной концентрации sPD-L1 и его связь с распространенностью процесса отмечены также у больных раком желудка, печени, немелкоклеточным раком легкого, некоторыми видами лимфом [16]. Для этих заболеваний продемонстрировано неблагоприятное влияние высоких уровней sPD-L1 на выживаемость пациентов.…”
Section: Discussionunclassified
“…В решении хотя бы части этих проблем важную роль может сыграть исследование растворимых форм PD-1 (sPD-1) и его лиганда (sPD-L1), обнаруженных относительно недавно в периферической крови, в том числе онкологических больных [16]. Происхождение sPD-1 и sPD-L1 пока не установлено, однако, как и растворимые формы других мембранных белков, они могут образовываться в результате 2 процессов: гидролитического отщепления внеклеточного домена или альтернативного сплайсинга мРНК нативной мембранной формы.…”
Section: Abstract: Immune Check-point Proteins Spd-l1 Spd-1 Renalunclassified
See 1 more Smart Citation